Interplay between sex, age, BMI, health-related quality of life, and coping strategies in amateur and professional athletes - Sapuppo, W.; Giaconni, D.; Monda, A.; Messina, A.; Saccenti, D.; Mineo, C. M.; Casillo, M.; Allocca, S.; Michelini, G.; Grgic, R. G.; Monda, V.; Lamanna, J.; et al. (Frontiers in Physiology, 2025)
Background/Objectives: The psychological well-being of athletes has garnered increasing interest due to its strong association with physical performance. While somatic indicators such as Body Mass Index (BMI) are routinely monitored in sports, the role of psychological resources—especially coping strategies—in shaping Health-Related Quality of Life (HRQoL) remains underexplored. This study aimed to investigate the influence of psychological and physical factors on HRQoL among amateur and professional athletes, controlling for sex, age, and BMI.